Simulasi dan Evaluasi Kinerja Protokol Distance Routing Effect Algorithm for Mobility (DREAM) Pada Vehicular Ad-hoc Network (VANET) Untuk Komunikasi Kendaraan dengan Infrastruktur - Imam Utomo; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Ad-Hoc Vehicle (VANET) is a network for wireless communication on vehicles that allows one node to another node to communicate with or without infrastructure. In VANET there are two modes of communication Vehicle-to-Vehicle (V2V) and Vehicle-to-Infrastructure (V2I). This paper is focused on discussing vehicle communication with infrastructure (V2I). In designing of VANET several problems arise, one of which is the selection of a routing protocol that matches the criteria and characteristics of the VANET network. In this paper, the protocol used is the Distance Routing Effect Algorithm for Mobility (DREAM), the protocol which will be simulated and analyzed based on a test-parameters that includes vehicles and variations of the RSU to establish a DREAM protocol suitable for use in VANET environments, DREAM protocol was chosen because the data transmission mechanism is related to the Road Side Unit (RSU). The simulation is performed using NS-2 for protocol simulation and SUMO is used for map simulation. The results of the DREAM protocol simulation will be analyzed based on test parameters namely packet delivery ratio (PDR), end-to-end delays, routing overhead and convergence The test results show the average value of PDR is 97,515%, the average value of end-to-end delay is 46,273 ms, the average value of routing overhead is 31,872 and the average value of convergence has is 548,207 ms..